2019
DOI: 10.1007/s11482-019-09739-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Residential Fragmentation and Quality of Life in Nairobi City, Kenya

Abstract: Residential fragmentation undermines integration by physically excluding some urban dwellers through walling, fencing and use of barriers limiting interactions. Research has shown that many cities in the Global South are experiencing spatial fragmentation issues associated with increasing inequalities, social exclusion and proliferation of gated communities. This results in distinct residential fragments with limited interactions and unequal quality of life (QoL) conditions of the residents of the fragments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Gibbons et al (2020) found that segregation is associated with clusters of poor health households albeit the final effect depends on races and ethnicities being poor-afro descent households the most affected group. Jimmy et al (2019) describe the association between residential segregation and quality of life in the city of Nairobi. They found a positive correlation between symbolic integration, safety, and quality of life related to housing in poor neighborhoods but a negative correlation of these variables in gated communities.…”
Section: Introductionmentioning
confidence: 99%
“…Gibbons et al (2020) found that segregation is associated with clusters of poor health households albeit the final effect depends on races and ethnicities being poor-afro descent households the most affected group. Jimmy et al (2019) describe the association between residential segregation and quality of life in the city of Nairobi. They found a positive correlation between symbolic integration, safety, and quality of life related to housing in poor neighborhoods but a negative correlation of these variables in gated communities.…”
Section: Introductionmentioning
confidence: 99%
“…Several findings are of particular interest. First, resilience can vary greatly on small spatial scales, from neighborhood to neighborhood, which is linked with high differences in the availability of livelihood opportunities [68] and the nested, often informal built environment in cities such as Pune [69]. Second, comparing the total migration and non-migration cohorts, we noted a significantly higher resilience of those that have moved to Pune than those that were born in the city.…”
Section: Discussionmentioning
confidence: 92%